دراسة تحليلية للبيئة اللوجيستية و البيئة القانونية للتجارة الالكترونية في الجزائر - بوسيف, عبد القادر أسامة; زاوي, أسماء (Ibn Khaldun University of Tiaret, 2022)
هدفت الدراسة الى تحليل كل من البيئة القانونية و البيئة اللوجستية و مدى تأثيرها على التجارة الالكترونية في الجزائر، وتوصلت الى أن البيئة القانونية هي جد مناسبة و تواكب العصرنة و ان التعديل الأخير في قانون التجارة الالكترونية أثمر عن مواد جد مناسبةومحفزة للتجارة الالكترونية في الجزائر، بالرغم من ذلك، لم تجد التجارة الإلكترونية بعد مكانتها في الجزائر ولم تحقق بعد الآن الانطلاقة المرجوة، يعود السبب في ذلك لكون البيئة اللوجستية لا تزال متأخرة و لا تواكب التطور الهائل الحاصل في هذا المجال، وأنه على الجزائر العمل على تطوير بيئتها اللوجستية بمسايرة التقدم التكنولوجي في العالم من أجل إعطاء دفعة للنهوض بهذا النوع من التجارة و إعتمادها كأسلوب حديث للتبادل التجاري في الجزائر. The study aimed to analyze both the legal environment and the logistics environment and their impact on e-commerce in Algeria. The study concluded that the legal environment is very suitable and keeps pace with modernity, and that the recent modification of the law on electronic commerce has resulted in very appropriate and stimulating articles for electronic commerce in Algeria. However, e-commerce has not yet found its place in Algeria and has not yet achieved the desired breakthrough, the reason is that the logistics environment is still lagging behind and not keeping pace with the enormous development of international e-commerce, and that Algeria should work to develop its logistics environment to keep pace with technological advances in the world in order to give impetus to the advancement of this type of commerce and its adoption as modern mode of commercial exchange in Algeria.
Keywords: Commerce électronique; Environnement juridique; Environnement logistique; Paiement électronique; البيئة القانونية; البيئة اللوجيستية; التجارة الإلكترونية; الدفع الإلكتروني